Low‐Field Borehole NMR Applications in the Near‐Surface Environment - Kirkland, C.M. (2020)
The inherent heterogeneity of the near subsurface (<200 m below the ground surface) presents challenges for agricultural water management, hydrogeologic characterization, and engineering, among other fields. Borehole nuclear magnetic resonance (NMR) has the potential not only to describe this heterogeneity in space nondestructively but also to monitor physical and chemical changes in the subsurface with time. Nuclear magnetic resonance is sensitive to parameters of interest like porosity and permeability, saturation, fluid viscosity, and formation mineralogy. Borehole NMR tools have been used to measure soil moisture in model soils, and recent advances in low‐field borehole NMR instrumentation allow estimation of hydraulic properties of unconsolidated aquifers. We also demonstrate the potential for low‐field borehole NMR tools to monitor field‐relevant biogeochemical processes like biofilm accumulation and microbially induced calcite precipitation at laboratory and field scales. Finally, we address some remaining challenges and areas of future research, as well as other possible applications where borehole NMR could provide valuable complementary data.